Đánh giá thực trạng và định hướng chuyển dịch cơ cấu hàng xuất khẩu Việt Nam thời kỳ 2005 - 2015 - Nguyễn, Hữu Khải (2011)
Tác giả: Nguyễn Hữu Khải, PGS,TS; Đinh Văn Thành, PGS,TS; Nguyễn Xuân Nữ, ThS; Phạm Thị Hồng Yến, ThS -- Từ khóa: Xuất khẩu